Degradation of glaciers in Dzungarian (Zhetisu) Alatau in the second half of the XX century - E. N. Vilesov; I. V. Seversky (Лëд и снег)
The features of spatial and temporal changes of glaciation in Djungarian Alatau for 44 years (1956–2000) are discussed in the paper. The evaluation of the glacier evolution based on the comparison of their morphometric characteristics, obtained by cataloging in 1956, 1990 and 2000. The aerial photographs are used for the first two periods, and Landsat satellite imageries with resolution of 15 m – for 2000. In addition the maps of glaciation in scale 1:25 000 were used for 1990 and 2000. The result of this work showed that during 44 years 341 glaciers melted, 227 glaciers dissolved, and their total number decreased from 1412 to 1298. The area of glaciers reduced from 841 to 528 km² (37.2%, to 0.85 %/year). The altitude of the firn line lifted by 65 m, from 3550 m up to 3615 m. Total ice volume diminished from 39.3 down to 20.2 km³ (39.2%, to 0.89 %/year). The average value of the glacier mass balance now equals –37,6 g/cm². The total area of glaciers in the region in 2010 is estimated at 465 km². According to the author’s forecast, glaciers in Djungarian Alatau may disappear to 2090.